(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Degenerative joint disease, also known as osteoarthritis (OA) is a common “wear and tear” disease. Typically, relentless repetitive motion deteriorates structural joints and causes inflammation is the underlying cause of this illness. Although it may affect any joint, it is usually seen in the hands, hips, knees, and spine. Bilateral hip osteoarthritis is described as a non-inflammatory degenerative condition of the hip joint that typically manifests in middle or late life. It is marked by acetabular dysplasia and growth or maturational abnormalities in the femoral neck and head. Pain experienced while moving or carrying weight is a prevalent symptom. As per Ayurvedic classics, the clinical presentation can be understood as Sandhigatavata in the initial stages and later as Asthigathavatha. Initial presentation includes difficulty in moving joints. Bony pain and joint discomfort are explained as Sakthi and Sandhi Shoolam and associated with Theevram balakshayam [severe weakness]. Internal and external applications of Sneha are the main therapeutic modalities explained in Asthi-majja gatha vatha chikitsa by Bruhathrayees. In Charaka samhitha, Ksheera, Basthi and Sarpi with Thiktha rasa Dravya are mentioned as the primary treatment along with Panchakarmas. Because it is the best of the four Snehas, cow’s ghee was chosen for the study. According to Sanskaranuvartana, Ghrita has the ability to change in order to absorb the properties of things that are introduced while retaining its original attributes. Ghee’s inherent property, oleate, settles Vata and Pitta while without raising Kapha. Phospholipid bilayers are the core elements of cell membranes. Molecules and ions are unable to directly get into or out of the cell via the lipid layer. We constantly need a lipid medium to go deeper. Asthi, Majja, and Sukra have been considered as deeper Dhatus in Ayurveda. The greatest administration for that is Samana accha snehapana. Degenerative joint condition can be effectively treated with traditional Asthigathavata Chikitsa.